(untitled) (Doctor Virtualis, 2025)
William of Ockham’s thought can be characterized as critical thinking. Through his arguments, Ockham engages in dialogue with past and contemporary authors, presenting new reasoning with the intent of introducing alternative methods and points of view. We want to highlight especially the themes related to the criticism of the realism of the universal, the criticism of the convergence between reason and faith and the criticism of the plenitudo potestatis, with the aim of indicating that in his work there is truly critical thinking. A philosophy that meticulously examines and validates certain arguments, not afraid to go against dominant and consolidated theses that, in his opinion, do not pass a critical examination.